Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3391/mbi.2018.9.1.05
|View full text |Cite
|
Sign up to set email alerts
|

Salinity tolerance of non-native suckermouth armoured catfish (Loricariidae: Pterygoplichthys sp.) from Kerala, India

Abstract: Introduced alien species bring potential adverse impacts on biodiversity and ecosystem functions. International shipping is an important vector for such unintentional introductions in aquatic environments. Therefore, in addition to climate change and eutrophication, increasing international shipping may enhance the spread of alien species into areas which have not previously been considered prone to alien invasions. One example of such development might be the recent invasion of the moss animal Pectinatella ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…As Pterygoplichthys spp. tolerate salinity up to 12‰ and are able to thrive under mesohaline conditions for extended periods (Kumar et al 2018), can easily invade the sensitive brackish water ecosystems of the lower Ganga, the Hooghly-Matla estuary, and the Sundarban mangrove ecosystems. The fish has been recorded from the extensive floodplain wetlands, natural ponds, and aquaculture farms existing along the lower Ganga basin, which are treasure troves of valuable indigenous fish species and also produce a large quantity of fish through capture, culture, and culture-based fisheries, which are at risk.…”
Section: Discussionmentioning
confidence: 99%
“…As Pterygoplichthys spp. tolerate salinity up to 12‰ and are able to thrive under mesohaline conditions for extended periods (Kumar et al 2018), can easily invade the sensitive brackish water ecosystems of the lower Ganga, the Hooghly-Matla estuary, and the Sundarban mangrove ecosystems. The fish has been recorded from the extensive floodplain wetlands, natural ponds, and aquaculture farms existing along the lower Ganga basin, which are treasure troves of valuable indigenous fish species and also produce a large quantity of fish through capture, culture, and culture-based fisheries, which are at risk.…”
Section: Discussionmentioning
confidence: 99%
“…Facilitated by the poorly documented and managed aquarium pet trade (Krishnakumar et al ., ), the South American loricariid catfishes of the genus Pterygoplichthys have established invasive populations in many countries of Asia, Africa, Europe and the Americas (Orfinger & Goodding, ), with widespread impact on native biodiversity and ecosystem services (Kumar et al ., , ; Nico et al ., ; Wei et al ., ). Despite a large number of published papers on the occurrence of Pterygoplichthys spp.…”
Section: Growth Mortality and Exploitation Parameters Of P Pardalismentioning
confidence: 99%
“…Tolerance to salinity is one of the significant physiological parameters that determine the rate of invasion success, stabilization and the pattern of dispersal of invasive species in the aquatic environment (Ashton et al, 2007) [41] . Although Pterygoplichthys spp is an inhabitant of freshwater but reported to exist in saline habitats (Bijukumar et. al., 2018) [42] .…”
Section: Effect On Carp Productionmentioning
confidence: 99%
“…Although Pterygoplichthys spp is an inhabitant of freshwater but reported to exist in saline habitats (Bijukumar et. al., 2018) [42] . The current study revealed that Pterygoplichthys spp.…”
Section: Effect On Carp Productionmentioning
confidence: 99%